Attentional bias in later stages of emotional information processing in female adolescents with borderline personality disorder - Ceumern-Lindenstjerna, Ina-Alexandra von; Brunner, Romuald; Parzer, Peter; Mundt, Christoph; Fiedler, Peter; Resch, Franz (Psychopathology, 2010)
Background: Bias in emotional information processing has been described in patients with borderline personality disorder (BPD). This study investigates whether adolescent patients with a diagnosis of BPD demonstrate abnormalities in attentional maintenance in viewing emotional faces. Sampling and Methods: Thirty female adolescents with a diagnosis of BPD, 29 female adolescents with mixed psychiatric diagnoses, and 30 healthy participants were tested with the visual dot probe task. The task involved showing photographs of actors with faces depicting neutral, negative, and positive expressions for 1,500 ms each. Results: Attentional bias to negative faces was not generally associated with BPD, but patients with BPD did show a strong correlation between current mood and attentional bias to negative faces. Only in adolescents with BPD did attention to negative faces narrow when they were currently in a state of negative mood. Conversely, both control groups avoided negative faces in conjunction with a decline in positive mood. Conclusions: This study indicates that borderline pathology is linked to an inability to disengage attention from negative facial expressions during attentional maintenance when in a negative mood. Based on these findings, mood-dependent therapeutic interventions focusing on attentional processes may represent a useful add-on to established therapies in patients with BPD.